Monetary Policy And Its Effects on Interest Rates and Ecomonic Stability - Salman Munthe; Muhammad Iqbal; Zulfa Ulya Salman Dalimunthe (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
Monetary policy is a crucial tool used by central banks to control key economic variables such as interest rates and economic stability. This study aims to explore the impact of monetary policy on interest rates and economic stability across various countries. Utilizing data from multiple periods and applying econometric analysis methods, this research finds that changes in monetary policy significantly affect interest rates and, in turn, impact economic stability. The results indicate that tight monetary policy, characterized by increased interest rates, tends to reduce inflation but may slow down economic growth in the short term. Conversely, loose monetary policy, with lower interest rates, can stimulate economic growth but risks increasing inflation. This study also highlights the importance of clear and credible communication from central banks to minimize uncertainty in financial markets and support economic stability. In conclusion, monetary policy plays a significant role in determining interest rates and maintaining economic stability. Central banks need to consider broader economic conditions and adopt a flexible and responsive approach to changes in both domestic and global economies.